Study of Rainwater Harvesting Implementation - Michelle N Gunawan Gunawan; Yunita Ismail Ismail (JIE Scientific Journal on Research and Application of Industrial System, 2020)
In recent years, because of the changes in the environment and an increase in the global population, there is an increase in the threat of water scarcity. Therefore, there a need for developing water supply systems that is sustainable and resilient. Rainwater harvesting (RWH) systems are a decentralized sustainable water supply system that has the potential to be implemented. Industries, as one of the sectors that will be affected, could potentially gain many benefits through the implementation of RWH systems. This paper is a literature review that has the objective of explaining the general concept of RWH systems and understanding several aspects that go into planning a rainwater harvesting system. RWH system is an old concept that has benefits and disadvantages. In planning an RWH system, there are many considerations and calculations. The catchment area, water storage, treatment train needs to be carefully chosen. In some cases of implementation, it has been observed that RWH systems have resulted in water and financial savings. There is much potential for further study of the implementation of RWH systems in industrial settings.